Review of Book “History of Abbasi Literature, Attitude and Art by Ezz al-Din Ismail - abu al-hasan amin moghadecci; moosa bayat; abdo al- vahid navidi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Academic books, along with other elements of higher education, are considered important tools toeducate students and prepare them to enter the society. So, the preparation of a book to be able to fulfil this aim seems necessary. Analyzing the academic books based on the standard features can help us accomplish such an important aim which constitutes  the pillars of higher education. This article seeks to examine the Qur'an based on structural, linguistic, content and form characteristics. Moreover, it tries to identify  the strengths and weaknesses of the book academic on the history of Arabic literature. The main results indicate that the apparent features such as artwork, page design and highlighs in writing are not taken into account.  The language of book is scientific, eloquent, without any ambiguity. The rules of grammar and Rhetoric have been fully observed. Proportionality between the amount of information and details of the book as a whole has not been met, but this has been considered in the context of the chapter. The book in question is not comprehensive and updated enough, and it has not been able to communicate well with other books at its level .Its writing style is not based on the academic criteria.